ANALISIS KEADILAN ORGANISASIONAL DALAM KEBIJAKAN MANAJEMEN SUMBER DAYA MANUSIA BAGI KARYAWAN PEREMPUAN - ADE YULIAR YULIAR (UIN Raden Mas Said Surakarta, 2019)
The purpose of this research is to analyze the implementation of organizational justice in human resource management (HRM) policies for female employees in Bank Syariah Mandiri. The research method used in this study is descriptive qualitative method. The results of this study conclude that in general, Bank Syariah Mandiri has carried out the practice of organizational justice in its Human Resources Management policy. This is proven by the policies implemented in career development, facilities provided by the bank for female employees such as mothers lactation and the provision of fair bonuses without gender discrimination.